Physical-territorial inventory thematic maps in the Veado stream water basin in Presidente Prudente, São Paulo, Brazil - Santos, Arthur Pereira dos; Saquetti, Paulo Barbosa; Ederli, Mateus; Felici, Elson Mendonça; Macena, Daniel Ângelo (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
The present work had the objective of producing the cartographic production of 4 thematic maps that compose the physical physical inventory of the watershed of the stream of Veado, located in Presidente Prudente - SP. The choice for referring maps was due to their individual particularities. The maps related to the topography of the study area (hypsometry and slope) are justified because there is a high number of floods in the region. As for the maps of land use and anthropogenic investments (land use and land cover and possible sources of contamination), it is justified by the current silting state of the basin. The choice of the study area represents the concern regarding the recovery of environmental aspects and conservation of the Veado stream basin area, mainly due to its local importance. Therefore, through geoprocessing and remote sensing techniques, the main physical characteristics and the main factors of possible contamination of the basin under study were collected and mapped. The results of the thematic maps discussed confirm the need for the preservation and recovery of degraded areas in the basin, which are almost completely degraded and urbanized, and it is necessary to establish adequate environmental planning techniques for their efficient restoration.